Left sided acute appendicitis with situs inversus in an elderly - an unusual case (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3818Journal of Chittagong Medical College Teachers' Association 2007: 18(1):29-31